2008
DOI: 10.1177/0963662506070159
|View full text |Cite
|
Sign up to set email alerts
|

Science knowledge and attitudes across cultures: a meta-analysis

Abstract: The correlation between knowledge and attitudes has been the source of controversy in research on the public understanding of science (PUS). Although many studies, both quantitative and qualitative, have examined this issue, the results are at best diverse and at worst contradictory. In this paper, we review the evidence on the relationship between public attitudes and public knowledge about science across 40 countries using a meta-analytic approach. We fit multilevel models to data from 193 nationally represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
511
6
15

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 541 publications
(562 citation statements)
references
References 28 publications
30
511
6
15
Order By: Relevance
“…Others find that the relationship between perceived risk and knowledge is 'chaotic' 47 suggesting a strong role for context. A more recent meta-analysis of science literacy as a correlate of non-upstream attitudes towards technologies (nuclear power, genetically modified organisms, stem cell research and so on) is comparatively definitive 48 . It found across 193 publicly available datasets that general knowledge of science has a weak but stable and positive effect on attitudes toward science and technology in their aggregate (0.08 for Cohen's D weighted regression coefficient), an effect that is weakened when general knowledge is compared to specific technologies, is non-significant in some cases (nuclear power and genetic medicine), and negative in other relationships (for example, environmental science knowledge and attitudes towards genetically modified foods).…”
Section: Familiarity Malleability and Judgement Uncertaintymentioning
confidence: 99%
“…Others find that the relationship between perceived risk and knowledge is 'chaotic' 47 suggesting a strong role for context. A more recent meta-analysis of science literacy as a correlate of non-upstream attitudes towards technologies (nuclear power, genetically modified organisms, stem cell research and so on) is comparatively definitive 48 . It found across 193 publicly available datasets that general knowledge of science has a weak but stable and positive effect on attitudes toward science and technology in their aggregate (0.08 for Cohen's D weighted regression coefficient), an effect that is weakened when general knowledge is compared to specific technologies, is non-significant in some cases (nuclear power and genetic medicine), and negative in other relationships (for example, environmental science knowledge and attitudes towards genetically modified foods).…”
Section: Familiarity Malleability and Judgement Uncertaintymentioning
confidence: 99%
“…The science communication community has recognized that a simple presentation of the scientific facts does not necessarily motivate public engagement, and meta-analysis has shown that science literacy is only weakly correlated with public attitudes toward controversial scientific issues such as climate change (Allum et al 2008). Values and motivated reasoning may bias information-seeking, interpretation and response to scientific issues (Kahan et al 2010;Kunda 1990), and communicators have been advised to convey climate information in ways that connect with audience values, increase the issue's relevance by emphasizing local consequences, and emphasize the co-benefits of emission reductions (Maibach et al 2008;Myers et al 2013;Bain et al 2012).…”
mentioning
confidence: 99%
“…This study has suggested that when males award experts responsibility for making important decisions about science in society, the way they use knowledge largely conforms to the deficit model (Allum et al, 2008;Bak, 2001;Wright & Nerlich, 2006): the more they know, the more supportive they become. This seems to typify the kind of male frequently described in the literature on gender and science, one that has much invested in hegemony of scientific institutions, and the one described so eloquently by Hayes:…”
Section: Discussionmentioning
confidence: 99%